2021
DOI: 10.1186/s13023-021-01961-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased chitotriosidase 1 concentration following nusinersen treatment in spinal muscular atrophy

Abstract: Background Studies regarding the impact of (neuro)inflammation and inflammatory response following repetitive, intrathecally administered antisense oligonucleotides (ASO) in 5q-associated spinal muscular atrophy (SMA) are sparse. Increased risk of hydrocephalus in untreated SMA patients and a marginal but significant increase of the serum/CSF albumin ratio (Qalb) with rare cases of communicating hydrocephalus during nusinersen treatment were reported, which confirms the unmet need of an inflamm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
0
14
0
3
Order By: Relevance
“…30 The increase in CHIT1 is thus probably not related to a therapeutic effect but might be caused by the repeated intrathecal administrations of an ASO leading to a mild inflammatory response, as suggested by Freigang et al (and supported by increased total protein levels in multiple studies). 16,31,32 After completion of the study, we analyzed CSF samples of 11/16 patients at month 30 of the treatment period, and found that four patients showed increased protein levels of which three had the highest CHIT1 levels in the study. No patients showed a pleocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The increase in CHIT1 is thus probably not related to a therapeutic effect but might be caused by the repeated intrathecal administrations of an ASO leading to a mild inflammatory response, as suggested by Freigang et al (and supported by increased total protein levels in multiple studies). 16,31,32 After completion of the study, we analyzed CSF samples of 11/16 patients at month 30 of the treatment period, and found that four patients showed increased protein levels of which three had the highest CHIT1 levels in the study. No patients showed a pleocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 No such data are currently available for individuals with SMA, except for a single recent study that concluded that baseline CHIT1 concentrations in CSF are elevated compared to controls and significantly increase over 14 months of treatment with nusinersen. 16 Other potentially interesting biomarkers for SMA patients are the neurodegenerative markers neurofilament light chain (NfL) and phosphorylated neurofilament heavy chain (pNfH), which were also found to be elevated in ALS and correlated with disease progression. 17 A recent study in infants with SMA type 1 showed that pNfH was elevated in plasma and CSF, correlated with multiple indicators of disease severity, and rapidly declined after treatment initiation with nusinersen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, chitotriosidase 1 concentrations in CSF (cCHIT1) were measured in the same cohort and at the same time as cGFAP (previously published in Ref. [ 22 ]).…”
Section: Methodsmentioning
confidence: 99%
“…cCHIT1 has recently been shown to be elevated in treatment‐naïve patients with SMA. 22 cNfL has been found to reflect disease severity and treatment response in pediatric SMA, 23 but still provides limited information in adult SMA because it overlaps with healthy controls and often shows no association with motor improvement. 24 , 25 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%